Social-Media addiction among students at public university / Suzila Mat Salleh ... [et al.] - Mat Salleh, Suzila; Hussin, Siti Najihah; Mohammed, Noor Hafiza; Hamzah, Siti Fatimah Mardiah; Mohamad Yusof, Hani Sakina; Ali, Noor Malinjasari (Universiti Teknologi MARA, Perlis, 2020)
Improvement in data-transfer speed and constant, continuous innovation in software and hardware, and humans' communication and networking through social-media networking have become much easier and breezier. Complex and data heavy information, such as high-definition videos, can be shared with million other users all over the planet at the ease of fingertips in just 1/1000th second. For the above reasons, social media have become a handy, crucial, and effective tool for users to propagate and seek useful and vital information. Therefore, the main objective of this paper is to identify a relationship between independent variables and dependent variable. The factors that have been analysed include intrinsic reasons, information-seeking and sharing, and social-media addiction. The study was conducted by using a quantitative method by distributing questionnaires to the degree students of a public university in the east coast of Malaysia. The respondents were from a group of students from the total population of 2,007 and the sample size was 327 students. The data from the questionnaires have been analysed by using the Statistical Package for the Social Science (SPSS) Version 23. Reliability analysis, frequency analysis, correlation analysis, and regression analysis are used in the research. The results prove that there are moderate and weak relationships among the variables.